Development of 55‐in. 8K AMOLED TV based on coplanar oxide thin‐film transistors and inkjet printing process. Issue 5 (29th April 2020) - Wu, Zhongyuan; Yan, Liangchen; Li, Yongqian; Feng, Xuehuan; Shih, Huaiting; Kim, Taejin; Peng, Yuqing; Yu, Jianwei; Dong, Xue
Abstract: In this paper, we presented 55‐in. 8K4K AMOLED TV employing coplanar oxide thin‐film transistor (TFT) backplane, top emissive inkjet‐printing organic light‐emitting diode (OLED) device, gate driver on array (GOA), and compensation technologies. It is so far the largest prototype AMOLED TV fabricated by using inkjet printing process with 8K resolution. It shows the stunning display quality, thanks to the high resolution and fast refresh frequency. It proves that the inkjet printing process is not only cost competitive but also can deliver premium display. Abstract : In this paper, we presented 55‐in. 8K4K AMOLED TV employing coplanar oxide thin‐film transistor (TFT) backplane, top emissive inkjet‐printing organic light‐emitting diode (OLED) device, gate driver on array (GOA), and compensation technologies. It is so far the largest prototype AMOLED TV fabricated by using inkjet printing process with 8K resolution.